PENGARUH PEMUNGUTAN PAJAK TERHADAP PAD PADA KANTOR RETRIBUSI DAERAH BANDAR LAMPUNG - Kumalasari, Nety; Sari, Pipit Novila (LPPM UNIVERSITAS BINA INSAN, 2021)
The purpose of this research is to discover the impact of our hotel tax and restaurant tax and original regional income from 2012 to 2018. The research was conducted in the local BPPRD in Lampung City, Bandar. The type of research is a case study, using interaction and documentation as data collection techniques. The data analysis komparatif technique is to use the t-test analysis tool to perform multiple merge analysis at the 5% significance level. The results of regression analysis show that from 2012 to 2018, the original and contemporaneous effects of hotel tax, restaurant tax and Bandar Lampung’s original regional income were significant. Variable independent hotel tax, restaurant tax and original regional income comparison, this technique uses purposeful sampling with necessary conditions. The population in this study is all selected as the sample company 84. It can then be concluded that the collection of hotel tax and hotel tax is compared with the original regional tax efektivitas.